Effect of aromatherapy on the pain of arteriovenous fistula puncture in patients on hemodialysis: a systematic review - Ayşegül Yıldız; Seda Şahan (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aims to determine the effect of aromatherapy used in reducing the pain caused by fistula puncture in hemodialysis patients. Design/methodology/approach - In this study, the effect of aromatherapy application on fistula puncture was analyzed and carried out by scanning the relevant literature. The literature review was conducted between August and October 2020. While reviewing the literature, the authors used "aromatherapy," "pain," "fistula," "puncture," "hemodialysis" keywords and various combinations of these; moreover, Google scientist, Pubmed, Cochrane, ScienceDirect, Web of Science, Medline and Ovid databases and studies, which were conducted in the last 10 years were reviewed. As a result of the literature review, 1183 studies were reached and seven of them were included in the study by taking the inclusion criteria into account. Findings - The randomized controlled studies are six studies and nonrandomized controlled experimental 1 study were added to the scope of the study and seven studies were included in the sample. In these studies, personal information forms developed by the researchers as data collection tools and the VAS scale, Numerical pain rating, the numeric rating scale were used to evaluate pain. Practical implications - It has been determined that aromatherapy application in hemodialysis patients has positive effects on reducing pain due to puncture fistula intervention. Originality/value - This study provides reduction or elimination of fistula needle insertion pain in hemodialysis patients.